CHILBLAINS AT ABBOTTABAD, A MODERATELY COLD WEATHER STATION - Raza, Naeem; Sajid, Mansoor ud Din; Ejaz, Amer (Journal of Ayub Medical College Abbottabad, 2006)
Background: Chilblains are quite often seen in various parts, in particular cold weather areas of Pakistan. Unfortunately, no studies have so far been carried out in Pakistan, to determine epidemiological aspects of chilblains. The objective of this study was to see the epidemiological patterns of chilblains at a moderately cold weather station. Methods: The study was conducted at Dermatology out patient department of Combined Military Hospital, Abbottabad from 1 Dec 2004 to 31 Mar 2005. All the patients fulfilling clinical criteria for the diagnosis of chilblains were registered. Every patient was interviewed in detail followed by thorough physical examination. Complete Blood Count, Urine Routine Examination and Anti Nuclear Factor were carried out in only those patients, having the disease of more than 3 years duration. A pre-designed proforma was filled separately for each patient. Results : Out of 111 patients, 67 (60.4%) males and 44 (39.6%) females were registered with the diagnosis of chilblains. Fifty nine (53.2%) patients were locals and 52 (46.8%) were non locals. Out door workers were 75 (67.6%). Onset in majority of the patients (42.3%) was in the age group 11-20 years. Family history of chilblains was present in 25 (22.5%) patients and 8 patients (7.2%) were smokers. The disease of longer duration was more common in females and locals. Conclusion: At moderately cold weather areas, out door workers and young adolescents are more likely to develop Chilblains. The disease of longer duration is more common among females and local residents. On the other hand, first episode or the disease of shorter duration is more common among non locals at moderately cold weather stations because of poor acclimatization and inadequate protection. Keywords : Chilblains, perniosis, cold weather injuries.